Content marketing: Gender and age differences in generation Z - Matic Sosic, Matea (Oeconomica Jadertina, 2024)
There is a growing number of users who expect personalised information and experiences that meet their personal needs and preferences. Therefore, companies emphasise that creating valuable content through digital channels is a vital element for the success and reputation of companies which also creates greater value for their users. The objective of this research is to determine the differences between the age and gender of Generation Z in relation to attitudes towards content posted on Instagram. The sample contained of 311 Generation Z social media users who were surveyed between April and June 2024. Non-parametric statistical methods such as the Mann Whitney U-test and the Kruskal-Wallis H-test were used in this study. The results show that there are statistical differences between age and attitude towards Instagram content. The research results show that there are partial differences between gender and users' activities on Instagram, but not in their intention to follow content in the future. There are also statistical differences between time spent on Instagram and attitude towards Instagram content. The results of this study contribute to the theoretical background of the literature on social media content marketing and also provide an empirical contribution for companies creating customized social media content, especially on Instagram, for Generation Z.
Keywords: Content marketing; Digital environment; Demographic features; Instagram; Generation Z